The Effect of Nepotism and Knowledge Sharing on the Performance of Academic Staff in Jordan: The Mediating Role of Trust - Hussein N.J.; Jaaffar A.H. (Richtmann Publishing Ltd, 2024)
The performance of employees is important for all organizations. The literature has focused on this performance in the business organization while few examined it in the educational context. Important variables such as knowledge sharing (KS), nepotism, and trust have not been widely investigated in educational settings in developing countries. The aim of this study is to investigate the impact of KS, nepotism, as well as trust on the performance of academic staff (PAS). In addition, the study investigates trust as a mediator in the link between nepotism-KS-PAS. Based on the review of theories and prior studies, the study proposed a positive effect of KS and trust on PAS while the negative effect of nepotism on PAS Trust will mediate these effects. The population of this study is the academic staff in Amman, the capital of Jordan. A total of 332 responses were collected using stratified random sampling. The data was collected via an online questionnaire. The data was analyzed using Smart PLS. The finding showed that KS, and trust affected positively PAS while Nepotism negatively affected PAS. Trust mediated the effect of KS on PAS. Universities have to establish a trusting culture to encourage KS. Nepotism is harmful to the performance of organizations and individuals. Universities have to eliminate the source of nepotism by implementing a fair and justice culture. 2023 Nisrin Jamal Hussein and Amar Hisham Jaaffar.